2002
DOI: 10.1111/j.1574-6941.2002.tb00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between ectomycorrhizal symbiosis and fluorescent pseudomonads on Acacia holosericea: isolation of mycorrhiza helper bacteria (MHB) from a Soudano-Sahelian soil

Abstract: Acacia holosericea seedlings were planted in 1-l pots filled with a soil collected from an Australian Acacia plantation in Southern Senegal. After 6 months of culture, mycorrhizosphere soil, roots, galls induced by root-knot nematodes and Rhizobium nodules were sampled from each pot. The diversity of this bacterial group was characterized by siderotyping (pyoverdine IsoElectric Focusing (IEF) analysis) and by restriction fragment length polymorphism (RFLP). The effect of these isolates on the establishment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The establishment of ectomycorrhizal symbiosis can be significantly improved by selected soil and mycorrhizosphere bacterial strains, called 'Mycorrhiza Helper Bacteria' (MHB; Frey-Klett et al, 2007). Despite this, direct effects of MHB on the pre-symbiotic survival and growth of ectomycorrhizal fungi in the soil have been well documented, highlighting the importance of fungal-bacterial interactions in the mycorrhiza helper process (Brule et al, 2001;Founoune et al, 2002;Schrey et al, 2005;Deveau et al, 2007). This has been demonstrated by the successful use of the controlled mycorrhization process for commercial reforestation in France.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of ectomycorrhizal symbiosis can be significantly improved by selected soil and mycorrhizosphere bacterial strains, called 'Mycorrhiza Helper Bacteria' (MHB; Frey-Klett et al, 2007). Despite this, direct effects of MHB on the pre-symbiotic survival and growth of ectomycorrhizal fungi in the soil have been well documented, highlighting the importance of fungal-bacterial interactions in the mycorrhiza helper process (Brule et al, 2001;Founoune et al, 2002;Schrey et al, 2005;Deveau et al, 2007). This has been demonstrated by the successful use of the controlled mycorrhization process for commercial reforestation in France.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several bacteria have been reported to be associated with the mycorrhizospheres of different host plants (3,4,14,16,17). The mycorrhizosphere, or more specifically the mycorrhizal hyphosphere, is the volume of soil influenced by the mycorrhizal hyphae, in contrast to the rhizosphere, which is the volume of soil influenced by plant roots (14).…”
mentioning
confidence: 99%
“…The phylogenetic analysis performed in this study showed that these fluorescent pseudomonads mostly belonged to Pseudomonas monteillii species. It has been demonstrated that one isolate of P. monteillii (isolate HR13) can stimulate the establishment of ectomycorrhizal symbiosis in tropical conditions (Founoune et al ., 2002b) and is considered as an MHB. This MHB effect has been recorded with different fungal isolates, such as S. dictyosporum , S. verrucosum , Pisolithus albus and P. tinctorius , on A. holosericea and other Australian Acacia species (Duponnois & Plenchette, 2003).…”
Section: Discussionmentioning
confidence: 99%